PENGARUH SOSIALISASI PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Devi, Novia; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2019)
Tax has a very important role in life of the state, especially in the implementation of development because taxes are a source of state cash income. This study aims to determine the effect of taxation sosialization and tax sanctions on compliance with annual tax returns for individual taxpayers. The research data include primary data obtained through questionmaires to respondens registered report SPT at KPP Pratama Batam Utara by using simple random sampling method. The population of this study is individual taxpayers who are registered as mandatory SPT as 83,506 taxpayers. The sample used in this study was 100. Data was processed using the SPSS version 22 program. The results of the study simultaneously Taxation Socialization and Tax Sanctions had a significant influence on the Compliance of Individual Taxpayer Annual Tax Returns Compliance. Partially Taxation Sanctions have a significant positive effect on Compliance with Annual Tax Returns Reporting while Taxation Socoalization does not have a significant influence on the Compliance of Annual Tax Returns. For the future efforts in carrying out socialization must be increased and more intensive by KPP Pratama Batam Utara and is expected to be able to enforce tax sanctions in accordance with applicable tax rules.